Design and Implementation of Home Security System Using Piezoelectric Sensor - Abdul Rashid, A. R.; Zakaria, F. (Universiti Sains Islam Malaysia, 2024)
A home security system using a piezoelectric sensor is designed to detect intrusion and unauthorized entry into the residential house. A piezoelectric sensor is used because of its capability that can convert mechanical pressure into electrical energy by the deformation of the crystal's structure. The relationship between the mechanical pressure and generated voltage is investigated by conducting an experiment using various pressure conditions and body weight. The relationship between pressure and body weight is directly proportional to the generated voltage. This home security system will control the home appliances based on the information given and send feedback when there is a security breach. The homeowner will receive a notification via a short message service (SMS) from an Arduino board equipped with a Global System for Mobile Communication (GSM)shield.